2016
DOI: 10.5468/ogs.2016.59.6.498
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum gonadotropin level and insulin resistance-related parameters in Korean women with polycystic ovary syndrome

Abstract: ObjectiveTo evaluate the relationship between serum gonadotropin level and parameters related to insulin resistance in Korean women with polycystic ovary syndrome (PCOS).MethodsThis retrospective study included 138 women aged 18 to 35 years who were newly diagnosed with PCOS according to the Rotterdam consensus. Participants were divided into three groups based on the serum luteinizing hormone to follicle-stimulating hormone (LH/FSH) ratio in the early follicular phase: group 1 (LH/FSH <1), group 2 (1.0≤ LH/FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Skałba et al [32] reported a significant correlation of serum AMH and total or low-density lipoprotein cholesterol levels with HOMA-IR and a significant negative correlation between high-density lipoprotein cholesterol and AMH levels. According to a previous study [33], total cholesterol level showed a positive correlation with the LH/ FSH ratio. However, other researchers reported no correlation of AMH and PCOM with insulin-linked metabolic parameters [34][35][36].…”
Section: Discussionmentioning
confidence: 71%
“…Skałba et al [32] reported a significant correlation of serum AMH and total or low-density lipoprotein cholesterol levels with HOMA-IR and a significant negative correlation between high-density lipoprotein cholesterol and AMH levels. According to a previous study [33], total cholesterol level showed a positive correlation with the LH/ FSH ratio. However, other researchers reported no correlation of AMH and PCOM with insulin-linked metabolic parameters [34][35][36].…”
Section: Discussionmentioning
confidence: 71%
“…The impact of porcine FSH on the elevation of peripheral glucose concentrations was about twice that found with human FSH. Park and Chun correlated the LH/FSH ratio with metabolic parameters in polycystic ovarian syndrome (PCOS) women and they concluded that most parameters correlated with insulin resistance [37]. It has also been suggested recently that high LH/FSH impaired insulin sensitivity resulting in elevations of blood glucose; this was confirmed in PCOS obese women [38].…”
Section: Discussionmentioning
confidence: 94%
“…In our study, the metabolic manifestations were more frequent with hyperandrogenemia rather than altered LH-FSH ratio. Similarly, another study did not find any correlation between different biochemical parameters related to insulin resistance with altered LH-FSH ratio [16,20].…”
Section: Discussionmentioning
confidence: 98%